It's time for nobody to release from anyone: gender, race and sexualities (Research, Society and Development, 2022)
This article is a collective product of the Social Work Topics subject, taught by Professor Dra. Elaine Nascimento at the Graduate Program in Public Policy at the Federal University of Piauí in 2019. The proposal was to discuss gender, race, sexualities and health in dialogue with the demands of the LGBTQIA+ population. The design of the discipline was not intended to be a merely conceptual discussion, it involved the discussion of texts by black authors, music clips also by black women and poetry and a certain level of exposure of the students (they were all women, in a total of five and also teacher) who were there, it was necessary to say what they were doing there and what they expected to find. The discipline's approach involved undressing itself to deal with an academic exchange of knowledge and experience that passed through affection, which we call quilombamento, based on a mirroring methodology, where all production would be built collectively, shared and shared. It means to say that the text written by one was read by another and defended by a third, the author of the text did the exercise of listening. The experience at first brought some discomfort, but as they said it was interesting, bonds of trust and respect were created even for this production. From these elements, the main objective of the article is to present a critical analysis of the relations between gender, race and sexuality, through the different crossings that the shared experience in the discipline allowed to visualize.